APLIKASI WEB CRAWLER UNTUK WEB CONTENT PADA MOBILE PHONE - Sarwosri Sarwosri; Ahmad Hoirul Basori; Wahyu Budi Surastyo (JUTI: Jurnal Ilmiah Teknologi Informasi, 2009)
Crawling is the process behind a search engine, which served through the World Wide Web in a structured and with certain ethics. Applications that run the crawling process is called Web Crawler, also called web spider or web robot. The growth of mobile search services provider, followed by growth of a web crawler that can browse web pages in mobile content type. Crawler Web applications can be accessed by mobile devices and only web pages that type Mobile Content to be explored is the Web Crawler. Web Crawler duty is to collect a number of Mobile Content. A mobile application functions as a search application that will use the results from the Web Crawler. Crawler Web server consists of the Servlet, Mobile Content Filter and datastore. Servlet is a gateway connection between the client with the server. Datastore is the storage media crawling results. Mobile Content Filter selects a web page, only the appropriate web pages for mobile devices or with mobile content that will be forwarded.